2017
DOI: 10.1186/s12920-017-0301-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of viral diversity for vaccine target discovery

Abstract: BackgroundViral vaccine target discovery requires understanding the diversity of both the virus and the human immune system. The readily available and rapidly growing pool of viral sequence data in the public domain enable the identification and characterization of immune targets relevant to adaptive immunity. A systematic bioinformatics approach is necessary to facilitate the analysis of such large datasets for selection of potential candidate vaccine targets.ResultsThis work describes a computational methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Investigation of the protein structure(s) of the dengue genes has allowed for inferences to be made about impacts to protein function such as virion shape dynamics (or breathing), binding site availability, roles in replication and virulence, and variation at defined epitopes (Table 1). Examination of entropy (disorder/variability) plots across the entire DENV proteome (Fig 1) does offer a useful perspective on the functional and structural determinants of viral evolution and diversity.. Tracking changes in variability within a proteome (or genome) due to different selection pressures over time is informative to predicting potential impacts on vaccine design and studies of viral molecular epidemiology (discussed in detail in sections 8 and 11.2) [12,13]. For example, it is notable that several internal genes, such as NS1 and NS2a, are noted to have substantial diversity (Fig 1).…”
Section: Setting the Stage For Evolution: A Primer On Denv Biology Ementioning
confidence: 99%
“…Investigation of the protein structure(s) of the dengue genes has allowed for inferences to be made about impacts to protein function such as virion shape dynamics (or breathing), binding site availability, roles in replication and virulence, and variation at defined epitopes (Table 1). Examination of entropy (disorder/variability) plots across the entire DENV proteome (Fig 1) does offer a useful perspective on the functional and structural determinants of viral evolution and diversity.. Tracking changes in variability within a proteome (or genome) due to different selection pressures over time is informative to predicting potential impacts on vaccine design and studies of viral molecular epidemiology (discussed in detail in sections 8 and 11.2) [12,13]. For example, it is notable that several internal genes, such as NS1 and NS2a, are noted to have substantial diversity (Fig 1).…”
Section: Setting the Stage For Evolution: A Primer On Denv Biology Ementioning
confidence: 99%
“…Structural binding predictions suggests that prevalent mutation in spike RBD region, N439K did not overlap with currently characterized epitopes of neutralizing antibodies recovered from human convalescent patient 47 , 48 , 49 . The importance of tracking such mutations within RBM region is demonstrated by a recent study that identified mutations enabling escape from RBD-directed neutralizing antibodies [ 60 ]. Our data indicate that the none of the currently characterized mutations within RBM region escape the five RBM targeted neutralizing antibodies used in this study.…”
Section: Resultsmentioning
confidence: 99%
“… Phytoplankton and zooplankton image classification using a non-linear multiple kernel learning approach [ 40 ]. Immuno-informatics Computational methodology pipeline to process, predict and analyze potential T cell epitopes using influenza A, dengue, West Nile hepatitis A and HIV-1 virus sequence data [ 41 ]. NetCTL-bases predictions of HLA-A2, -A3 and -B7 supertype-restricted Zaire ebolavirus T cell epitope canidates [ 42 ].…”
Section: Manuscript Submission and Reviewmentioning
confidence: 99%